RESISTENSI BEBERAPA KLON TEH (CAMELLIA SINENSIS L.) TERHADAP SERANGAN TUNGAU JINGGA (BREVIPALPUS PHOENICIS GEIJSK) - ANITA HANNA ATMOWIDJOJO (Research Center for Biology-Indonesian Institute of Sciences, 1985)
ANITA HANNA ATMOWIDJOJO. 1985. Resistancy of some tea (Camellia sinensis L.) clones to scarlet mites (Brevipalpus phoenicis Geijsk). Berita Biologi 3 (1) : 1-4. Scarlet mite (Brevipalpus phoenicis Geijsk) is an important pest of tea culture in Indonesia. Several means can be used to control this pest such as the use of pesticides, biological control, and the use of tea resistant clones.The last mentioned method is considered to be the best and the most effective.Most of the tea estates in Indonesia nowadays use clones as new planting materials and their resistance to scarlet mite is known to vary.In the present study, sixteen clones were compared for their resistance.The results showed that clones PS 324 and TRI 2024 were the most resistant to scarlet mite nfestations.